The Habit of watching English movies in improving vocabulary: What do the students say? - Adrefiza, Adrefiza; Wulandari, Kiki; Haryanti, Reny (Langue (Journal of Language and Education), 2024)
This study investigates students' perceptions of how watching English movies influences vocabulary development. A descriptive qualitative approach was used, involving a questionnaire completed by 50 students and semi-structured interviews with eight purposefully selected students from the English Language Education Study Program (ELESP) at the Faculty of Education, Universitas Jambi. Findings reveal that students perceive a positive impact from the habit of watching English movies, indicating it as beneficial for vocabulary enhancement. The selected participants met two criteria: regular experience watching English movies and completion of core courses in Listening, Speaking, Reading, Grammar, and Vocabulary. The study highlights improvement primarily in receptive and productive vocabulary, especially in informal language, idioms, and slang. It is recommended that lecturers integrate English movie watching into classroom activities or suggest it as a supplementary tool to foster vocabulary growth and overall language proficiency.